The Librarian’s Image and the Perception of Libraries; A Barrier to Library Development in Ghana - Asamoah-Hassan, Helena R. (Ghana Library Journal, 1997)
The issue of the low public image of librarians and how the profession is perceived is constituting a hindrance to library development. This issue has been a long running one the world over, probably beginning soon after the profession came into being . In Ghana, the situation is not different because Alemna (1994) confirms this as a problem hindering the progress of the library profession in the country. Is this situation of the low public image of the librarian really true or are people just building on hearsays to arrive at that conclusion? If it is not true, why then is it so persistent and seemingly intractable?